2011
DOI: 10.1016/j.csr.2010.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Sources and distribution of organic matter in northern Patagonia fjords, Chile (∼44–47°S): A multi-tracer approach for carbon cycling assessment

Abstract: We investigated the provenance of organic matter in the inner fjord area of northern Patagonia, Chile (~44-47° S), by studying the elemental (organic carbon, total nitrogen), isotopic (δ 13 C, δ 15 N), and biomarker (n-alkanoic acids from vascular plant waxes) composition of surface sediments as well as local marine and terrestrial organic matter.Average end-member values of N/C, δ 13 C, and δ 15 N from organic matter were 0.127 ± 0.010, -19.8 ± 0.3‰, and 9.9 ± 0.5‰ for autochthonous (marine) sources and 0.040… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 57 publications
(54 reference statements)
7
52
1
3
Order By: Relevance
“…The precision, calculated by replicate analysis of the internal standard, is 0.03 ‰ for δ 13 C and 0.08 ‰ for δ 15 N. Some of the bulk organic geochemical results used in this study were previously reported in Sepúlveda et al (2011). …”
Section: Inorganic Geochemistrymentioning
confidence: 94%
See 2 more Smart Citations
“…The precision, calculated by replicate analysis of the internal standard, is 0.03 ‰ for δ 13 C and 0.08 ‰ for δ 15 N. Some of the bulk organic geochemical results used in this study were previously reported in Sepúlveda et al (2011). …”
Section: Inorganic Geochemistrymentioning
confidence: 94%
“…The N/C value obtained on the river samples is very similar to the average of the seven soil samples (N/C = 0.0680) but it is preferred because it is known that N/C ratios are affected by transport in rivers and by weathering in soil profiles (Bertrand et al, 2010). Although bulk sedimentary δ 13 C data can also be used to calculate F terr (e.g., Sepúlveda et al, 2011), we prefer using the N/C data because δ 13 C values of marine organic matter are affected by several processes such as changes in productivity (e.g., Bickert, 2006). The values of F terr obtained using the two methods are highly positively correlated (r=0.94, p<0.0001).…”
Section: Calculation Of a Terrestrial Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from fjords in Chile (Bertrand et al, 2012;Sepúlveda et al, 2011;Silva et al, 2011), New Zealand (Hinojosa et al, 2014;Knudson et al, 2011;Smith et al, 2015), east Greenland (Andrews and Vogt, 2014) and Svalbard (Winkelmann and Knies, 2005) reported a significant influence of freshwater inflow on their geochemical composition and suggest a common decreasing gradient of terrigenous-derived organic-and inorganic material from the inner fjords towards the open ocean. In contrast to these findings, Munoz and Wellner (2016) found terrigenous deposits to occur predominantly in the outer bay of an Antarctic fjord.…”
Section: Introductionmentioning
confidence: 99%
“…Fjords comprise a substantial part of the coastal environments and are important sites for carbon burial due to their high inorganic and organic sedimentation rates (Hedges et al, 1997;Knies, 2005;Knudson et al, 2011;Ludwig et al, 1996;Raymond and Bauer, 2001;Sepúlveda et al, 2011;Smith et al, 2015;St-Onge and Hillaire-Marcel, 2001;Syvitski et al, 1987) but only a very few studies exist using surface sediments to investigate modern fjord environmental settings. Studies from fjords in Chile (Bertrand et al, 2012;Sepúlveda et al, 2011;Silva et al, 2011), New Zealand (Hinojosa et al, 2014;Knudson et al, 2011;Smith et al, 2015), east Greenland (Andrews and Vogt, 2014) and Svalbard (Winkelmann and Knies, 2005) reported a significant influence of freshwater inflow on their geochemical composition and suggest a common decreasing gradient of terrigenous-derived organic-and inorganic material from the inner fjords towards the open ocean.…”
Section: Introductionmentioning
confidence: 99%